Beneficiamento do caulim duro das bacias dos rios Capim e Jari através do processo de agregação seletiva - Paulo Sergio Rueda Criscuolo (2009)
For the last years, the papermaking market has been demanding for more and more noble fillers. In the case of coated papers, the demand for high brightness kaolin has increased, which is becoming a growing challenge to their producers, especially those of fine kaolins. It is known that the finer is the kaolin, the finer are the contaminants, and due to this fact the respective beneficiation process becomes extremely complicated and high cost.As the conventional beneficiation processes usually require high brightness ores to obtain high brightness products, and the availability of high brightness ores is usually very small, the marketing of these high brightness products has been continuously shownlower profitability, even becoming not viable in some cases.The purpose of this study was to develop a beneficiation process that allows toproduce high brightness products from low brightness ores, being economically viable, in order to meet mainly the papermakers growing demands. The development was divided into two stages, where in the first one a special beneficiation process called selective aggregation was tested, which aimed the removal of titanium contaminants by dispersantdosage excess and high rotation centrifugation. As the result of this stage was not satisfactory, there was a second one, where the mechanism of selective aggregation has been changed, using this time as reagents sodium hydroxamate and a modified magnethite. Measuring the kaolin optical properties and the respective residual level of TiO2 , it was possible to conclude that the modified process developed in the second stage reached the proposed goals.The whole development was conducted in the kaolin laboratory and pilot plant in the CDM (Center for Mineral Development) of Vale, in Santa Luzia, Minas Gerais.